Shear rate equations for yield stress fluids in couette flow - Leong, Y.K. (Malaysian Journal of Science, 1999)
The accuracy of the Krieger-Maron, power law and Yang-Krieger equations for calculating the shear rate of three specific Herschel-Bulkley fluids (r = + Kr) couette flow within the annulus of a concentric cylinder was assessed. The chosen fluids have a shear rate exponent n of 1, 1/2 and 1/3. The accuracy for all three equations was found to depend upon the fluid model, stress level and radius or gap ratio E of the concentric cylinders. With the Krieger-Maron equation, the shear rate is only accurate in the fully sheared regime for all n and E. In contrast both the power law and Yang-Krieger equations are accurate in both the plug and fully sheared flow regimes. For both equations, the largest absolute error generally decreases with increasing E and decreasing n and is usually located near the transition from plug to fully sheared flow. In terms of the largest absolute error, the Yang-Krieger is more accurate